Students’ school engagement in face-to-face set-up - Villanueva, Christopher E. (Animo Repository, 2023)
The COVID-19 Pandemic changes the ways of social connections and gathering. For the past two years, students have acquired knowledge through Learning Management Systems. Subjects’ contents and student outputs are presented virtually. Different pandemic stories of learning and engagement success and failures emerge and shape the perception of students affecting their thoughts, motivation, emotional responses, relationships, the way transactions are done at home, and how engagements are expected at school. This paper aims to understand and design a program for students returning to an on-site learning set-up and implement student activity protocols to assess, and process students’ experience from activities and events participated in an online mode. Descriptive statistics are used to describe the response and participation of the respondents in the survey, and the interpretations were based on the sentiment analysis of thoughts and feelings about returning to full implementation of on-campus classes and non-academic school activities. Gaps between academic and non-academic engagements are discussed. Results describe the condition of the respondents, which are necessary for academic faculty and event organizers.